Association of serum zinc levels with the atherogenic index in obese adults - Anjum, Nishat; Jhumu, Sayeda Anjum; Sultana, Morium; Munmun, Rydwana (International Journal of Research in Medical Sciences, 2026)
Background: Obesity is associated with dyslipidemia and micronutrient imbalances, including altered serum zinc levels. The atherogenic index of plasma (AIP) is an emerging biomarker of cardiovascular risk. This study evaluated the association between serum zinc and AIP in obese adults. Methods: In this comparative cross-sectional study at Sylhet MAG Osmani Medical College, Bangladesh (July 2022–June 2023), 60 participants were enrolled and divided by body mass index (BMI) according to WHO Asian guidelines: group A (obese, BMI ≥25 kg/m², n=30) and group B (healthy, BMI 18.5–24.9 kg/m², n=30). Serum zinc, triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) were measured, and AIP was calculated as log₁₀ (TG/HDL-C). Results: The mean BMI was significantly higher in group A compared to group B (30.13±2.39 versus 21.88±1.87 kg/m²; p<0.001), while age and gender distribution were similar. Group A exhibited higher TG (188.53±36.93 versus 145.30±32.22 mg/dl; p<0.001) and lower HDL-C (39.43±5.93 versus 47.43±7.93 mg/dl; p=0.001). Serum zinc was significantly reduced (10.15±1.03 versus 13.13±1.34 µmol/l; p<0.001), and AIP was higher (0.32 versus 0.12; p<0.001) in obese participants compared to healthy subjects. Regression analyses showed a strong negative correlation between BMI and serum zinc (r=−0.797, p<0.001), a moderate negative correlation with TG (r=−0.591, p<0.001), and a moderate positive correlation with HDL-C (r=0.616, p<0.001). Conclusion: Obese adults exhibited lower serum zinc levels and elevated AIP. BMI and lipid parameters, particularly TG and HDL-C, significantly predicted serum zinc status, highlighting the interrelationship between obesity, dyslipidemia, and micronutrient deficiency.